Comparison of Stresses Induced by Fiber Post, Parapost and Casting Post in Root Canals by Photoelasticity Method - Rezaei, Aliakbar; Soltani, Fereidoon; Vafaei, Fariborz; Khoshhal, Masoumeh; Ayatollahi, Majid Reza; Soltani, Naser; Nejati, Morteza (Iranian Endodontic Journal, 2010)
INTRODUCTION: Many studies have been performed to evaluate the stress distribution around endodontic posts; those which compared posts composed of different materials are rare. The aim of this study was to compare stresses induced in dentin by three structurally different posts using photoelasticity method. MATERIALS AND METHODS: Nine blocks of PSM-5 Photoelastic material with 45×45×10 mm dimension were prepared. In each block, a canal 9 mm in length and 0.8 mm in width was drilled. Blocks were divided into 3 groups of three each. In the first group, the canals were prepared for insertion of Fiber Post with 1.25 mm width. In the second group, the canals were prepared for insertion of ParaPost with 1.25 mm width and the canals in the third group were prepared for casting post similar to the above samples. Casting Post pattern was made by Duralay resin and casted by Ni-Cr alloy. All posts were cemented in canals with Panavia cement. The stresses were evaluated in the polariscope under three different conditions: 1) without load, 2) with 135 N vertical load, and 3) with 90 N oblique load (26° inclination to post long axis). The fringe orders in the cervical, middle and apical regions of the posts were evaluated and compared with each other.RESULTS: Application of the vertical load induced a high stress concentration (FO=4) in the apical region of the ParaPost, while lower stress was observed in the middle (FO=2) and cervical region (FO=2+). Fiber Post and Casting Post showed even stress distribution (FO=2+). High stress concentration was detected with the application of oblique force in the cervical region of ParaPost (FO=5) and Casting Post (FO=3+). Fiber Posts fractured before reaching 90-N loading force. CONCLUSION: The stress distribution around Fiber Post and Casting Post were constant in comparison with ParaPost. Fiber Post with 1.25 mm width was not recommended in situations with high oblique stresses.